Effect of biosurfactant on ammonia removal from anaerobically digested swine wastewater by multi soil layering treatment bioreactors. Issue 19 (23rd August 2020) - Guo, Junyuan; Jia, XiaoJuan; Yang, Lan; Zhang, Guojun; Zhang, Lu
ABSTRACT: A biosurfactant was harvested from anaerobically digested swine wastewater (ADSW) and employed to enhance ammonia removal in a comparative study using two multiple soil layer bioreactors (MSLs). Results showed that toxicity of the biosurfactant to microorganisms was negligible within the experimental concentration range. Optimal dose of the biosurfactant in MSLs to remove ammonia from ADSW was 0.1 CMC (Critical Micelle Concentration) under different hydraulic loading rate (HLR). For instance, when the HLR was adjusted as 80, 120, 160, and 200 L/(m 2 ·d), the average ammonia removal efficiency in MSL without biosurfactant addition was appeared as 85.6%, 89.2%, 85.2% and 84.1%, respectively, after enhanced by 0.1 CMC of the biosurfactant under the same condition, the average ammonia removal efficiency was improved to 90.1%, 92.6%, 90.3%, and 87.4%, respectively. Inlet ammonia concentration obviously affected ammonia removal, the average ammonia removal efficiency increased rapidly to 93.0% and 89.1% in MSLs (with and without biosurfactant) along with the increasing inlet ammonia concentration from 800 mg/L to 1000 mg/L, and subsequently dropped to 78.9% and 79.7% with a further increase in the inlet ammonia concentration to 1400 mg/L. These results showed that the biosurfactant effectively enhanced ammonia removal by using MSL. Thus, the construction of MSL represented an effective means of reducing ammonia pollution caused by swine wastewater, and the use of biosurfactant was assuredly a promising and feasible option for enhancing the biological activity in MSL bioreactor. GRAPHICAL ABSTRACT: UF0001